Potential of monolaurin based food-grade nano-micelles loaded with nisin Z for synergistic antimicrobial action against Staphylococcus aureus. (September 2016) - Sadiq, Sara; Imran, Muhammad; Habib, Huma; Shabbir, Saima; Ihsan, Ayesha; Zafar, Yusuf; Hafeez, Fauzia Yusuf
Abstract: Monolaurin is recognized as an emulsifier and antimicrobial agent with potential use in the food industry. Empty and nisin loaded monolaurin nano-micelles were successfully developed for the first time in the present study. Encapsulation of nisin had not significantly increased the mean diameter of loaded monolaurin nanoparticles (MNPs), which was calculated as 59.19 ± 8.66 nm as compared to 54.7 ± 5.6 nm for empty MNPs. The zeta potential of empty and nisin containing nanoparticles was observed as −45.1 ± 2.6 mV and −40.5 ± 2.12 mV, respectively. Nisin was loaded with an excellent encapsulation efficiency of 78.8 ± 2.5% in MNPs. The FTIR analysis had confirmed that the encapsulation of nisin into MNPs was based on electrostatic attraction only. Ultra-microscopic studies by scanning electron microscopy (SEM) and atomic force microscopy (AFM) had revealed homogenous distribution with maximum height of 53 and 57 nm for empty and loaded MNPs, respectively. Furthermore, nisin loaded MNPs had synergistically controlled the growth of Staphylococcus aureus ATCC-25923 for up to 164 h in vitro . The stability of nisin loaded nanoparticles based on the results of antimicrobial behavior and zeta potential suggest their potential application in food systems to avoid food borne illness outbreaks. Highlights: Innovative nano-carrier system based on glycerol monolaurate (ML) was developed. Nisin Z encapsulated in monolaurin nano-particles (MLNPs) for its enhanced stability. MLNPs exhibited an average size of less than 60 nm and charge higher than −45 mV. Nisin loaded MLNPs demonstrated synergistic antimicrobial effect against Staphylococcus aureus . Atomic force microscopy revealed nisin release by pore-formation from MLNPs.